(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
Many studies in the field of education have reflected on the importance of imagination in the learning process. Considering the interest of surveying the portion of these studies that think about the theme of imagination from the specific interests of teaching and learning history, a bibliographical review of the literature was carried out in this article. We sought to verify what has been produced and what are the gaps in the scientific literature on the theme of imagination in the teaching-learning of history. The identified works allow us to perceive that the references that address the theme of imagination in the teaching-learning of history are scarce and are based on old references, but unanimous in defending the importance of this mental ability in the individual’s relationship with historical knowledge. It was also noted the need to develop new studies that propose to contribute to the distinction between imagination in the broad sense and historical imagination.